Developing intensive, short-term courses for public health—Creation and outcome evaluation of the Skills for Health and Research Professionals (SHARP) program at the Columbia University Mailman School of Public Health - Welbourn, Abigail L.; Brennan, Kasey J. M.; Baccarelli, Andrea A. (Frontiers in Public Health, 2024)
Short, intensive education programs provide an under-utilized avenue for public health professionals to learn and apply the latest methods and technologies. We report on the creation and implementation of the Skills for Health and Research Professionals (SHARP) program at the Columbia University Mailman School of Public Health. The self-sustaining, concise, intense educational format equips participants with concrete skills, better enabling them to respond to complex public health challenges.